Acute scrotal complications of Ventriculoperitoneal Shunting in pediatric practice. Case report and literature review - D. N. Shedrov; D. K. Shelkoshveev; M. V. Pisareva; E. V. Morozov (Вестник урологии, 2019)
We analyzed the experience of a rare complication of ventriculoperitoneal shunting – migration of the abdominal catheter into the scrotum through the non-obliterated vaginal scion with the development of acute symptoms from the scrotum. The case histories of two patients with short-term complications of ventriculoperitoneal shunting were studied, general clinical and instrumental examination data were presented, and surgical tactics for this condition were analyzed. The problem of these complications is shown as related, requiring the collective participation of urologists, surgeons, neurosurgeons This review provides general guidelines for managing patients with the described complication based on published data and our own experience.